The Value of Connectivity: High-Speed Broadband Internet and Real Estate Prices - Thomas A. Fackler; Oliver Falck; Simon Krause (CESifo GmbH, 2024)
Governments worldwide subsidize rural broadband expansion to address the urban-rural connectivity divide, but the economic benefits and costs remain unclear. This paper examines the causal effect of high-speed Internet on real estate prices and evaluates the fiscal effectiveness of rural broadband subsidies. Using a spatial regression discontinuity design and comprehensive micro-data, our identification strategy exploits variation at state borders from German states' broadband expansion policies. We find that high-speed Internet availability (16 Mbit/s) increases rents by 3.8 percent ( exteuro17/month) and sale prices by 8 percent ( exteuro14,700) compared to slower access at the discontinuity, with diminishing returns at higher speeds. The capitalization effects are demand-driven, as evidenced by increased broadband uptake, migration, and remote work adoption, while property supply remains unaffected. A cost-benefit analysis within the marginal-value-of-public-funds framework shows the economic surplus exceeds deployment costs for 90 percent of households, while property owners benefit from subsidies through higher property prices.
Keywords: D60; H40; H70; L86; R20; 330; high-speed broadband internet; real estate prices; capitalization effect; policy evaluation; local public finance; spatial RDD; MVPF